Analysis of user satisfaction on the discord application using the Electronic Service Quality (E-SERVQUAL) method - Jesica Pitos Dwi Putri; Pradita Eko Prasetyo Utomo; Dewi Lestari (Journal of Computer-based Instructional Media, 2026)
The rise of digital communication platforms based on the internet has heightened the demand for service quality that aligns with user expectations. Discord, a Voice over Internet Protocol and Instant messaging application, is widely embraced by various communities; however, complaints regarding system stability, service responsiveness, and user support continue to arise. This study aims to evaluate user satisfaction with the Discord application using the Electronic Service Quality (E-SERVQUAL) method. Employing a descriptive quantitative approach, data was collected through an online questionnaire from 128 active Discord users in Indonesia, selected via purposive sampling. The research instrument was crafted based on the six dimensions of E-SERVQUAL: Efficiency, Reliability, Fulfillment, Privacy, Responsiveness, and Contact, comparing users’ expectations with their perceptions. The findings reveal that all dimensions of E-SERVQUAL exhibit negative gap values. The Total Electronic Service Quality score of -0.44 indicates that the overall service quality of Discord falls short of user expectations, with the Responsiveness dimension showing the most significant gap. The study concludes that enhancing service quality, particularly in Responsiveness and user support, is vital for improving user satisfaction.